Proficiency levels of teachers' digital competence: a review of recent international frameworks - Angelina Lorelí Padilla-Hernández; Vanesa M.ª Gámiz-Sánchez; M.ª Asunción Romero-López (Innoeduca, 2019)
The development of teachers’ digital competence is an educational goal that has been recognized in the field of educational policy through international frameworks and models. This article addresses three frameworks for teachers’ digital competence that were published between 2016 and 2017. The objective is to analyze the contributions of these frameworks to the understanding of the development of this competence. The method consisted of both documentary research and content analysis at a qualitative, descriptive and comparative approach, focused on two variables: proficiency levels of competence and aspects to foster competence development. The findings of the first variable pointed to three ways in which the teachers’ digital competence could improve: the creation of learning environments, the improvement of educational practice, and the spread of experiences of educational use of information and communication technologies (ICT). Regarding the aspects that lead to the development of this competence, the frameworks showed: reflection, continuous practice, collaboration and the participation of teachers in the field of education and ICT. Finally, some challenges for both the approach of the frameworks and their implementation are highlighted, as well as critical issues about the institutional support to teachers in order to promote the development of their digital competence.